Two trends in canon law from 1150 to 1250 - (:unkn) unknown (Universidad de Buenos Aires. Facultad de Filosofía y Letras. Instituto de Filosofía Alejandro Korn. Sección de Filosofía Medieval., 2003)
Canon Law in the 12th and 13th centuries has often been associated with the growth of the papal monarchy. Without denying such connection, this paper aims to suggest that it brought about elements that helped to challenge the central place of the pope in Christendom. First, in broad lines, the use of Matthew 16,18 (Tu es Petrus) and the Translation of the Empire by Gratian, Innocent III and Innocent IV, which evolved to support the increasing authority of the pope in temporal affairs, are discussed. Some aspects of this use that could give, and eventually gave, shape to a doctrine on the deposition of the pope, are then pointed out.
Fil: Cesar, Floriano Jonas. Universidad de San Judas Tadeu; Brasil.
Keywords: FILOSOFÍA MEDIEVAL; FILOSOFÍA POLITÍCA; IGLESIA CATÓLICA; EDAD MEDIA; CLEROS; MONARQUÍA; PODER POLITÍCO; PODER ECLESIÁSTICO; DERECHO ECLESIÁSTICO